2008
DOI: 10.1111/j.1872-034x.2008.00371.x
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic transplantation of hepatocyte sheets fabricated with temperature‐responsive culture dishes

Abstract: These results imply the usefulness of hepatocyte sheets in ectopic transplantation, as well as the need of trophic factors for hepatocyte survival.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Hepatocytes with more than 90% viability were plated on a 35-mm temperature-responsive PIPAAm culture dish (UpCell; CellSeed, Tokyo, Japan) at a density of 8 × 10 5 cells/dish. Hepatocytes were cultured as described previously (28,31) at 37°C for the first 24 h, and then the medium was replaced daily with fresh culture medium with supplemental reagents containing 0.5 μg/ml insulin (Wako Pure Chemical Industries, Osaka, Japan) and 10 ng/ml epidermal growth factor (EGF) (Invitrogen, Carlsbad, CA) until cell sheet harvesting (9).…”
Section: Methodsmentioning
confidence: 99%
“…Hepatocytes with more than 90% viability were plated on a 35-mm temperature-responsive PIPAAm culture dish (UpCell; CellSeed, Tokyo, Japan) at a density of 8 × 10 5 cells/dish. Hepatocytes were cultured as described previously (28,31) at 37°C for the first 24 h, and then the medium was replaced daily with fresh culture medium with supplemental reagents containing 0.5 μg/ml insulin (Wako Pure Chemical Industries, Osaka, Japan) and 10 ng/ml epidermal growth factor (EGF) (Invitrogen, Carlsbad, CA) until cell sheet harvesting (9).…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, function, such as urea synthetic rate, decreased below the control level (Hasirci et al, 2001). In addition to collagen-based materials, many other materials and methods are proposed (Kano et al, 2008;Katsuda et al, 2010;Torok et al, 2011), which will steadily improve tissue transplantation techniques. In the future it is expected that simpler, easier, more effective and more practical transplantation techniques will be developed.…”
Section: Hepatocytes Transplantation: Where or How Are Hepatocytes Trmentioning
confidence: 99%
“…One advantage of using cultured cell sheets is that they eliminate the need for scaffolds, precluding the strong inflammatory responses that are typically induced when biodegradable scaffolds are broken down. Several studies have shown the potential of this technology for reconstitution of the cornea [13] and the myocardium [14], and in hepatocyte transplantation [15] and renal tube epithelial cell transfer [16].…”
mentioning
confidence: 99%